Question
upstudy study bank question image url

20) \( \begin{array}{l}2 x+3 y=-12 \\ 5 x-3 y=-9\end{array} \)

Ask by Owen Tucker. in the United States
Nov 22,2024

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( x = -3, y = -2 \)

Solution

Solve the system of equations \( 2x+3y=-12;5x-3y=-9 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}2x+3y=-12\\5x-3y=-9\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=-\frac{12+3y}{2}\\5x-3y=-9\end{array}\right.\) - step2: Substitute the value of \(x:\) \(5\left(-\frac{12+3y}{2}\right)-3y=-9\) - step3: Multiply the terms: \(-\frac{5\left(12+3y\right)}{2}-3y=-9\) - step4: Multiply both sides of the equation by LCD: \(\left(-\frac{5\left(12+3y\right)}{2}-3y\right)\times 2=-9\times 2\) - step5: Simplify the equation: \(-60-21y=-18\) - step6: Move the constant to the right side: \(-21y=-18+60\) - step7: Add the numbers: \(-21y=42\) - step8: Change the signs: \(21y=-42\) - step9: Divide both sides: \(\frac{21y}{21}=\frac{-42}{21}\) - step10: Divide the numbers: \(y=-2\) - step11: Substitute the value of \(y:\) \(x=-\frac{12+3\left(-2\right)}{2}\) - step12: Simplify: \(x=-3\) - step13: Calculate: \(\left\{ \begin{array}{l}x=-3\\y=-2\end{array}\right.\) - step14: Check the solution: \(\left\{ \begin{array}{l}x=-3\\y=-2\end{array}\right.\) - step15: Rewrite: \(\left(x,y\right) = \left(-3,-2\right)\) The solution to the system of equations is \( x = -3 \) and \( y = -2 \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve the system of equations \(2x + 3y = -12\) and \(5x - 3y = -9\), you can use the elimination method. First, add the two equations together to eliminate \(y\): \[ (2x + 3y) + (5x - 3y) = -12 - 9 \\ 7x = -21 \\ x = -3 \] Now, substitute \(x = -3\) into either equation to find \(y\). Using the first equation: \[ 2(-3) + 3y = -12 \\ -6 + 3y = -12 \\ 3y = -6 \\ y = -2 \] The solution to the system of equations is \(x = -3\) and \(y = -2\). Now, if you want to check your solution, simply plug \(x\) and \(y\) back into both original equations. If both equations are satisfied, you've got it right!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy